Information Brokerage: An Entrepreneurial Approach to Information Services in Nigeria (Global Journal of Management and Business Research, 2012)
This article focuses on the genesis of and rationale for information consultancy #x2013; also known as information brokerage or independent information profession (IIP) - as a profession in Nigeria. This may not be an easy task since Nigeria is, relatively, a newcomer to this field. This paper takes a look at the possibility and viability of information consultancy as is being practised in some developing and developed countries. It concludes that it is a good venture to be embarked upon. The article also highlights the challenges confronting the profession, especially in the areas of policy formulation, power generation, ICT, skill acquisition, managerial ability, report writing and data analysis, and recommends the way forward for would-be information brokers.
Keywords: Information brokerage; entrepreneur; information services; library and information service profession; independent information profession